Case Report: Unusual Manifestation of KIT Negative Systemic Mastocytosis - Cáceres-Nazario, Beatriz (Am J Hematol Oncol, 2016)
Aggressive systemic mastocytosis is a rare hematologic neoplastic disease that presents with a poor prognosis and low survival rate. It typically manifests with symptoms associated to mast cell release of bioactive substances, causing anaphylaxis, flushing, autonomic and hemodynamic instability, gastric distress and headache. Moreover, more than 95% of cases are related to a mutation in codon 816 of the KIT gene, located on human chromosome 4q12 which codes for a type III receptor tyrosine kinase. We present a 78 year-old Hispanic man diagnosed with the aggressive subtype of systemic mastocytosis, who had an atypical manifestation and a KIT negative variant. The diagnosis was confirmed based on pathologic and serologic findings which included mast cell infiltration of the spleen and bone marrow, malignant ascites and an unusually elevated serum tryptase.